2023
DOI: 10.1590/1678-5150-pvb-7142
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nonpathological intrascleral cartilage in the domestic sheep (Ovis aries)

Abstract: Birds, cartilaginous and teleost fish, reptiles, and some amphibians have intrascleral cartilage and/or bone; however, these are rarely reported in therian mammals. This study aimed to investigate and characterize a nonpathological formation of cartilage in the posterior sclera of sheep macroscopically, histologically, and by immunohistochemical exam (IHC). Ninety eyes from 45 domestic sheep were collected, underwent gross examination, fixed in formalin, and embedded in paraffin for the microscopical assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Affected goats included both sexes and a wide range of breeds and ages. In a recent study by Teodoro et al, intrascleral cartilage was also demonstrated both histopathologically and immunohistochemically in 60 globes (67%) of 37 sheep (82%) 49 . To the best of our knowledge, these two studies are the first to report on intrascleral bone or cartilage in the normal globe of a mammalian species, 48,49 resembling the scleral ossicles of birds 50 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Affected goats included both sexes and a wide range of breeds and ages. In a recent study by Teodoro et al, intrascleral cartilage was also demonstrated both histopathologically and immunohistochemically in 60 globes (67%) of 37 sheep (82%) 49 . To the best of our knowledge, these two studies are the first to report on intrascleral bone or cartilage in the normal globe of a mammalian species, 48,49 resembling the scleral ossicles of birds 50 .…”
Section: Discussionmentioning
confidence: 78%
“…In a recent study by Teodoro et al, intrascleral cartilage was also demonstrated both histopathologically and immunohistochemically in 60 globes (67%) of 37 sheep (82%). 49 To the best of our knowledge, these two studies are the first to report on intrascleral bone or cartilage in the normal globe of a mammalian species, 48,49 resembling the scleral ossicles of birds. 50 The presence of bone or cartilage in the sclera may restrict age-related changes in globe dimensions and refractive errors.…”
Section: Discussionmentioning
confidence: 90%